Agile for everybody : the essentials of Agile and Lean (O'Reilly, 2017)
"This video describes the core values, rhythms, and practices of Agile and Lean in accessible and jargon-free terms, and provides concrete and actionable strategies for bringing the best of Agile and Lean to your organization."--Resource description page